2022
DOI: 10.3389/fpubh.2022.873596
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of COVID-19 vaccines in reducing the incidence, hospitalization, and mortality from COVID-19: A systematic review and meta-analysis

Abstract: BackgroundVaccination, one of the most important and effective ways of preventing infectious diseases, has recently been used to control the COVID-19 pandemic. The present meta-analysis study aimed to evaluate the effectiveness of COVID-19 vaccines in reducing the incidence, hospitalization, and mortality from COVID-19.MethodsA systematic search was performed independently in Scopus, PubMed via Medline, ProQuest, and Google Scholar electronic databases as well as preprint servers using the keywords under study… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
59
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(87 citation statements)
references
References 97 publications
4
59
0
Order By: Relevance
“…The results of comparing the two mRNA vaccines showed that the incidence of AEs and serious AEs for BNT162b2 was slightly lower than that for mRNA-1273 [49]. Therefore, the outcomes of the quantitative BR model for both pre-and post-authorization in the study were consistent with the published literature results [48,50].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The results of comparing the two mRNA vaccines showed that the incidence of AEs and serious AEs for BNT162b2 was slightly lower than that for mRNA-1273 [49]. Therefore, the outcomes of the quantitative BR model for both pre-and post-authorization in the study were consistent with the published literature results [48,50].…”
Section: Discussionsupporting
confidence: 85%
“…Beyond collecting data, network meta-analysis, in which multiple treatments are being compared, can be used for advanced analysis. In contrast, real-world data showed that mRNA-based vaccines were comparable to or had better safety profiles than viral-vector vaccines [48]. The results of comparing the two mRNA vaccines showed that the incidence of AEs and serious AEs for BNT162b2 was slightly lower than that for mRNA-1273 [49].…”
Section: Discussionmentioning
confidence: 93%
“…Globally, governments have implemented public health measures, including quarantine/stay at home orders, social distancing, lockdowns and closures of various social or commercial venues, travel restrictions, vaccination, and more, to help mitigate the transmission of the SARS-CoV-2 virus [1,2] Immunization is critical to protecting the public from the deleterious health consequences of COVID-19 infection and facilitating the reopening of the economy and society at-large. [3,4,5,6] For the latter, vaccine certificates have been introduced as a hybrid approach of gating access to certain privileges (e.g., cross-border travel, return to work, access to certain shared public spaces and venues, etc.) under the condition of vaccination against COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…Vaccination is among the most advantageous health interventions due to its positive effects on population health and the economy. COVID-19 vaccination has effectively prevented the disease and lowered the risk of hospitalization and death [4]. This protection, however, declines over time due to waning immunity and, most importantly, the emergence of new virus variants [5].…”
Section: Introductionmentioning
confidence: 99%